Modeling the smartness or smart development levels of developing countries' cities - Prince Antwi-Afari; De-Graft Owusu-Manu; S. Thomas Ng; George Asumadu (Journal of Urban Management, 2021)
The race towards smart city status, influenced by the perceived benefits of innovation and sustainability in smart city concepts, has engendered the need to measure the smartness/smart development levels of developing countries' cities to improve upon urban infrastructures. However, various strategies for determining cities' smartness/smart development levels are mostly inconclusive by not considering all the dimensions in urban space in their assessments. This study adopted a fuzzy synthetic evaluation (FSE) technique to model the smartness/smart development levels of a developing country city using a six-dimensional framework which provides a comprehensive perspective on the characterization of urban frameworks of cities. A positivism research philosophy using deductive approach and purposive sampling technique was adopted. Quantitative data were collected from experts using a close-ended questionnaire in which 76 responses were retrieved. The study modeled eight indicators for each of the six dimensions using FSE to determine the smartness/smart development level index of each dimension towards the determination of the overall smartness/smart development level index of the developing country city. After analysis, the developing country city and each of the six dimensions used to characterize the city were determined as fairly developed. The implications of such level of ranking meant that the city is below the acceptable smart city status, and hence, improvement should be made in policy applications along the 48 identified indicators such as empowering human resources, sustainable resource consumption, etc., to propel the six dimensions towards smart city. This study could also serve as a theoretical model for determining the smartness/smart development levels of developing countries' cities. The study also reveals aspects in the urban framework where policy makers and urban developers could target to improve the smartness/smart development levels of cities towards the smart city status.
Keywords: 710; Smart city; Urban framework; Fuzzy synthetic evaluation; Indices; Developing countries. TOPICS; Applications; Planning; Governance